ANALYSIS THE EFFECT OF GALVANIZED AND UNGALVINEZED CARBON STEEL PIPE ON THE WELDING RESULT BASED ON MIYANO NUMBER FORMULA IN API 581 - Al Ghazaly, Ekky
In this study, microstructure, mechanical properties and chemical composition of weld metal and heat-affected zone (HAZ) of galvanizing and un-galvanizing pipe weld were investigated. In the welding experiments, ASTM A53-B steel specimens with galvanizing and un-galvanizing coating conditions were used. The specimens taken from pipe low carbon steel NPS 4 with schedule 40 were cut and rolled in order to obtain a flat steel. The galvanize and un-galvanize specimens were welded using a tungsten inert gas welding machine with current 90 A. Following the welding, microstructure, hardness and chemical composition of weld metals and HAZ were investigated. From the results, we tried to establish a relationship between microstructure, hardness and chemical composition of weld metals and HAZ. From the results of the hardness tests, it was seen that the weld metals of galvanize specimens and un-galvanize specimens had different values with the same parameter of weld, whereas un-galvanized specimen had higher hardness than galvanize specimen. Furthermore, the result of chemical composition was found that both of specimen had low Miyano number those the value is under 100. As a result, considering the welding with TIG, it was observed that the galvanize coating had no influence on Miyano number of a low carbon steel. Thus, taking into consideration the changing welding method such as SMAW should be used with respect to get the more variation on Miyano Number based on API 581. .